Evolutionary remodeling of a remnant GET pathway factor into PEX38, an essential peroxin - Chethan K. Krishna; Stefan Gaussmann; Hirak Das; Martin Jung; Silke Oeljeklaus; Michael Sattler; Bettina Warscheid; Vishal C. Kalel; Ralf Erdmann (Proceedings of the National Academy of Sciences, 2026)
PEX19 is a cytosolic receptor that directs membrane proteins posttranslationally to peroxisomes, as well as to mitochondria, lipid droplets, and the endoplasmic reticulum. A comprehensive Trypanosoma PEX19 interactome analysis uncovered PEX38 as an essential Euglenozoa-specific peroxin. PEX38 contains distinct domains that bind the cochaperone Hip and the PEX3-binding motif of PEX19, suggesting a role in stabilizing membrane proteins and preventing premature membrane docking. PEX38 illustrates functional repurposing in organelle biogenesis. It originated from a remnant of the GET/TRC pathway, typically responsible for the targeting of tail-anchored (TA) proteins to the endoplasmic reticulum. While most components of this machinery are absent in Euglenozoa, PEX38 has been retained and adapted to mediate peroxisomal membrane protein targeting. This evolutionary adaptation is unique to Euglenozoa. Because the PEX19–PEX38 interaction is essential for parasite viability and PEX38 has no human homologs, this complex is a promising therapeutic target against trypanosomatid parasites.